Detection of buried pipes using a shear wave ground surface vibration technique - Muggleton, J. M.; Papandreou, B. D.; Brennan, M. J. [UNESP] (My University, 2012)
A major UK initiative, entitled 'Mapping the Underworld', is seeking to address the serious social, environmental and economic consequences arising from an inability to locate the buried utility service infrastructure without resorting to extensive excavations. Mapping the Underworld aims to develop and prove the efficacy of a multi-sensor device for accurate remote buried utility service detection, location and, where possible, identification. One of the technologies to be incorporated in the device is low-frequency vibro-acoustics, and the application of this technology for detecting buried infrastructure is currently being investigated. Here, a shear wave ground vibration technique for detecting buried pipes is described. For this technique, shear waves are generated at the ground surface, and the resulting ground surface vibrations measured, using geophones, along a line traversing the anticipated run of the pipe. Measurements were made at a test site with a single pressurized polyethylene mains water pipe. Time-extended signals were employed to generate the illuminating wave. Cross-correlation functions between the measured ground velocities and a reference measurement adjacent to the excitation were then calculated and summed using a stacking method to generate a cross-sectional image of the ground. The wide cross-correlation peaks caused by high ground attenuation were partially compensated for by using a generalized cross-correlation function called the smoothed coherence transform. To mitigate the effects of other potential sources of vibration in the vicinity, the excitation signal was used as an additional reference when calculating the generalized cross-correlation functions. For two out of three tests, the pipe was detected, indicating that this technique will be a valuable addition to the Mapping the Underworld armoury.
Keywords: Cross correlations; Cross sectional image; Cross-correlation function; Economic consequences; Excitation signals; Generalized cross correlations; Reference measurements; Service infrastructure; Mapping; Sensors; Shear waves; Water pipelines; Signal detection